2009
DOI: 10.1016/j.virol.2008.12.025
|View full text |Cite
|
Sign up to set email alerts
|

High replication fitness and transmission efficiency of HIV-1 subtype C from India: Implications for subtype C predominance

Abstract: HIV-1 subtype C has been the predominant subtype throughout the course of the HIV-1 epidemic in India regardless of the geographic region of the country. In an effort to understand the mechanism of subtype C predominance in this country, we have investigated the in vitro replication fitness and transmission efficiency of HIV-1 subtypes A and C from India. Using a dual infection growth competition assay, we found that primary HIV-1 subtype C isolates had higher overall relative fitness in PBMC than subtype A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…[54][55][56] A breakdown of HIV-1 in Yunnan includes CRF07_BC (18.9%), CRF08_BC (39.1%), and CRF01_AE (22.4%) 57 ; pol sequences in newly diagnosed HIV-infected individuals from Dehong county, Yunnan, showed that subtype C accounted for 43.1%, URF for 18.4%, CRF01_AE for 17.7%, B for 10.7%, CRF08_BC for 8.4%, and CRF07_BC for 1.7% 58 ; near-full-genome sequencing results show that many new CRFs have been generated in this region. [59][60][61][62] In India, subtype C is the predominant circulating subtype, [63][64][65][66] irrespective of the route of transmission, 67,68 and has been reported as one of the parental strains of CRF07_BC and CRF08_BC in China. 69 URFs of subtype C with B¢ are increasing, especially in the northeastern states.…”
Section: Hiv-1 Molecular Epidemiologymentioning
confidence: 99%
“…[54][55][56] A breakdown of HIV-1 in Yunnan includes CRF07_BC (18.9%), CRF08_BC (39.1%), and CRF01_AE (22.4%) 57 ; pol sequences in newly diagnosed HIV-infected individuals from Dehong county, Yunnan, showed that subtype C accounted for 43.1%, URF for 18.4%, CRF01_AE for 17.7%, B for 10.7%, CRF08_BC for 8.4%, and CRF07_BC for 1.7% 58 ; near-full-genome sequencing results show that many new CRFs have been generated in this region. [59][60][61][62] In India, subtype C is the predominant circulating subtype, [63][64][65][66] irrespective of the route of transmission, 67,68 and has been reported as one of the parental strains of CRF07_BC and CRF08_BC in China. 69 URFs of subtype C with B¢ are increasing, especially in the northeastern states.…”
Section: Hiv-1 Molecular Epidemiologymentioning
confidence: 99%
“…There are conflicting reports regarding the rate of disease progression of subtype C relative to that of other subtypes (12,(15)(16)(17)(18). While there is general agreement that subtype C has a transmissibility rate at least equal to those of other M group subtypes (19,20), some studies have reported increased transmissibility of subtype C compared to subtypes A and D (21)(22)(23). Furthermore, the higher heterosexual transmission of subtype A than of subtype D (24) may have contributed to the expansion of subtype A in Uganda (9).…”
mentioning
confidence: 99%
“…The in vitro replication fitness and transmission efficiency of primary isolates of HIV-1 subtypes C was higher than subtype A primary isolates [34]. This probably explains the predominance of subtype C strains in spite of introduction of subtype A strains in India more than decade and half ago.…”
Section: Indian Hiv Strainsmentioning
confidence: 95%